The concept of the legal form of agricultural production - Костур, О. Д. (Theory and practice of jurisprudence, 2016)
The article deals with the rules of national law and scientific doctrine on the definition of «legal form of legal entity». Through analysis derived definition of «legal form of agricultural production» and the basic elements of this legal concept. Based on the conclusions of the study to improve the current legislation of Ukraine.